Increasing Active Participation in the Catholic Liturgy through Faith Formation in the Diocese of Atambua - Yohana Aek Klau (PT FORMOSA CENDEKIA GLOBAL, 2026)
The active participation of the faithful in the liturgy of the Catholic Church is a manifestation of a full appreciation of the faith, but in pastoral practice there is still a passive and formalistic involvement of the faith. This condition confirms the importance of understanding and appreciation of faith as an internal factor that affects the quality of liturgical participation. This research aims to analyze the role of understanding and appreciation of faith in increasing the active participation of the people in the celebration of the Church's liturgy. The research used a qualitative approach with a descriptive design, which was carried out in one of the parishes of the Catholic Church in East Nusa Tenggara Province. Data were collected through in-depth interviews with 10 informants consisting of 6 parishioners, 2 liturgical officers, and 2 pastoral administrators, and were complemented by direct observation during the liturgical celebration and documentation study. Informants are selected deliberately based on active involvement in the liturgical life of the parish. Data analysis is carried out thematically through the stages of data reduction, data presentation, and conclusions drawn. The results of the study show that the active participation of the faithful in the liturgy is greatly influenced by the level of understanding of faith, the experience of spiritual appreciation, and the continuous development of faith.